Detecting Potential Fraud in Village Fund Management from the Fraud Hexagon Theory Perspective - Apriyanto, Gaguk; Kumar, Abdul Malik (AKRUAL: JURNAL AKUNTANSI, 2025)
Research Background: Village heads and village officials are the most dominant perpetrators of corruption at the village level in Indonesia. The village head's leadership role is crucial in managing village government, including the village budget. Introduction/Main Objectives: This study aims to analyze the influence of the fraud hexagon elements on the potential for fraud in village fund management, with religiosity as a moderating variable. Method: A sample of 200 village officials was analyzed using PLS-SEM through SmartPLS 4.0. Result: The results indicate that the effectiveness of the internal control system and the competence of village officials have a significant positive effect, while organizational culture and political connections have a significant negative effect. Compensation suitability and village officials' morality have no significant effect. Religiosity only moderates the relationship between the effectiveness of the internal control system and fraud, but does not moderate the relationships between compensation suitability, organizational culture, village officials' competence, village officials' morality, and political connections. Conclusion: Based on the research results described relevant agencies are advised to continue strengthening and improving their village fund management oversight systems to minimize the potential for fraud. Village fund managers are expected to demonstrate a strong sense of responsibility in carrying out their duties, as any actions that suggest fraud, even if only suspicion, cannot be justified.